2019
DOI: 10.1101/714824
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bayesian Correlation is a robust similarity measure for single cell RNA-seq data

Abstract: AbstractAssessing similarity is highly important for bioinformatics algorithms to determine correlations between biological information. A common problem is that similarity can appear by chance, particularly for low expressed entities. This is especially relevant in single cell RNA-seq (scRNA-seq) data because read counts are much lower compared to bulk RNA-seq.Recently, a Bayesian correlation scheme, that assigns l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…We generated a series of gene networks for each condition by varying the cutoff values of MI. From our initial exploration, we found that activating links were favored in the network construction, probably because of the nature of scRNA-seq data (Sanchez-Taltavull et al, 2019). To select different numbers of activating and inhibitory links, we varied the MI cutoffs for positive and negative interactions.…”
Section: Constructing Context-specific Grcsmentioning
confidence: 99%
“…We generated a series of gene networks for each condition by varying the cutoff values of MI. From our initial exploration, we found that activating links were favored in the network construction, probably because of the nature of scRNA-seq data (Sanchez-Taltavull et al, 2019). To select different numbers of activating and inhibitory links, we varied the MI cutoffs for positive and negative interactions.…”
Section: Constructing Context-specific Grcsmentioning
confidence: 99%
“…Accurate and robust estimation of the strength of gene co-expression relationships is the key to reliable inference of gene co-expression networks. Since single-cell gene expression data contain excess zero counts and relatively inaccurate low counts due to both technical and biological variability [35,29], the conventional Pearson or Spearman's correlation coefficients are often not reliable for single-cell gene expression data, especially for genes whose expression values are highly sparse ( Figure 1) [36,20]. In our previous work, we proposed a statistical method, scImpute, to address the excess zeros in scRNA-seq data [29].…”
Section: A Robust Estimator For Measuring Gene Co-expression Strengthmentioning
confidence: 99%
“…However, these two measures cannot provide a robust estimation of gene co-expression given the sparse scRNA-seq data with substantial technical noises and biological heterogeneity [20,21].…”
Section: Introductionmentioning
confidence: 99%